(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The aim of the Erasmus+ project OpenPass4Climate (OP4C) (2022-2025) is to use Open Badges (OBs) to acknowledge and promote learner engagement in climate action. In order to promote a common digital recognition ecosystem for sustainability competences, the project links stakeholders from the business sector and higher education institutions across five European nations (Belgium, France, Italy, Portugal, and Spain). Using a cross-sectoral approach, this study investigates the use of OBs in eco-pedagogical and corporate social responsibility (CSR) efforts. The open recognition system combines self-assessment, activity validation, and digital badge attribution via a Moodle-based platform created by CSCI (Novara, Italy), aligned with the European GreenComp framework and its KSA (Knowledge, Skills, Attitudes) approach. This poster presented participants’ perspectives on OB usability, motivational value, clarity, perceived recognition, and integration into Human Resources (HR) and educational structures, based on findings from ten focus groups conducted across the five partner countries: five with business stakeholders and five with education stakeholders. Business sector stakeholders emphasized the necessity of OB alignment with national certification systems and professional frameworks like the Erasmus Skills Passport. Meanwhile, educational stakeholders stressed the importance of linking badges to curricular flexibility, teacher training, and non-formal learning recognition. The poster presented practical suggestions for integrating OBs into institutional procedures, fostering inclusive digital ecosystems, and facilitating the transition toward more sustainable and socially responsible workplaces and educational environments. This poster contributeed to the ePIC 2025 discussion on reliable open recognition methods by highlighting methodological insights, cross-cultural findings, and badge design frameworks. Keywords: Open recognition, climate engagement, GreenComp, open badges